Imagine - H. C. Palmer (Symphony in the Flint Hills, 2019)
Introduction: Imagine someone finding Herefords and sycamores unnatural and uninteresting, one who lives inside caves of tall buildings, who wears dark glasses against the sunlight. Here, out of curiosity or even despair, he considers a creek bed for the first time, uneasy that shadows are diffused in timber and tall grass and unaware he has walked over a trail of wheel ruts and through the bowl of an old buffalo wallow.